Identity and mobility through personal ornaments in Upper Paleolithic cantabrian hunter-gatherer societies: Insights from Llonín cave (Asturias, Spain) - Daniel Pérez-García de los Salmones; David Cuenca-Solana; Borja González-Rabanal; Ana B. Marín-Arroyo; Elsa Duarte-Matías; Marco de la Rasilla-Vives (PLoS ONE, 2026)
The use of personal ornaments is considered a milestone in human cognitive evolution and the development of complex behavior. The Cantabrian region in the north of the Iberian Peninsula served as a hub of occupation and intergroup contact throughout the Upper Paleolithic, and acted as a climatic refugium during the Last Glacial Maximum (LGM – 25,000–19,000 years ago), constituting a key region for understanding the social and symbolic structures and interactions of hunter-gatherer groups. This study analyses personal ornaments recovered from the Upper Paleolithic stratigraphical sequence at Llonín Cave (Asturias, Spain), spanning from the Upper Solutrean to the Azilian (c. 21.8–11 kya cal BP), that comprises the regional largest and most diverse assemblage. The combination of taxonomic, biometric, taphonomic, and use-wear analyses reveals rarely documented patterns, such as diachronic shifts in the site’s role as an importer and producer of ornaments, the varying social significance of their use, and the strategies for raw material procurement. Furthermore, the study identifies evidence of coastal-inland interactions, allowing the reconstruction of the complete chaîne opératoire for ornament manufacture. These findings provide a framework for reinterpreting the use of personal ornaments among Paleolithic hunter-gatherer groups, facilitating critical discussions on key dimensions such as mobility and identity.